2014
DOI: 10.1186/s13550-014-0058-y
|View full text |Cite
|
Sign up to set email alerts
|

Bone Scan Index as a prognostic imaging biomarker during androgen deprivation therapy

Abstract: BackgroundBone Scan Index (BSI) is a quantitative measurement of tumour burden in the skeleton calculated from bone scan images. When analysed at the time of diagnosis, it has been shown to provide prognostic information on survival in men with metastatic prostate cancer (PCa). In this study, we evaluated the prognostic value of BSI during androgen deprivation therapy (ADT).MethodsProstate cancer patients who were at high risk of a poor outcome and who had undergone bone scan at the time of diagnosis and durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 14 publications
(25 reference statements)
2
20
1
Order By: Relevance
“…We found a significant association between the bone scintigraphy response (according to PCWG2) and OS, although this finding was based on a small number of observations, whereas no association between the BSI response and OS was detected. These results conflict with recent reports of the BSI as a response marker in mCRPC settings (20,21). The discrepancy could be a result of the extensive skeletal involvement of our cohort; in such a setting, BSI measurement might not perform adequately in detecting changes.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We found a significant association between the bone scintigraphy response (according to PCWG2) and OS, although this finding was based on a small number of observations, whereas no association between the BSI response and OS was detected. These results conflict with recent reports of the BSI as a response marker in mCRPC settings (20,21). The discrepancy could be a result of the extensive skeletal involvement of our cohort; in such a setting, BSI measurement might not perform adequately in detecting changes.…”
Section: Discussioncontrasting
confidence: 99%
“…The automated BSI for the assessment of skeletal tumor burden in patients with prostate cancer is an example of such a diagnostic tool. The BSI has been proven to be valuable for prognostication, prediction, and response assessment in prostate cancer patients (11,(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…However, the small sample size in this subgroup analysis is a clear limitation. Another limitation would be a variation in time between baseline and follow-up bone scan, when compared with the time used in previous aBSI studies [9][10][11][12][13]. Despite these limitations, this study shows that changes in aBSI are associated with survival even at earlier stages of the disease in high-risk PCa patients.…”
Section: Discussionmentioning
confidence: 88%
“…It has also been shown to be a potential tool for monitoring response in patients with metastatic castration-resistant prostate cancer (mCRPC) treated with docetaxel, new androgen signalling inhibitors, or tasquinimod [8][9][10][11][12]. Results from these studies have shown a strong correlation between aBSI and overall survival (OS), with a cut-off value of 1% of metastatic burden [4,13]. The importance of using baseline and follow-up values of aBSI to analyse the change in aBSI to predict the outcome has also been demonstrated in patients with advanced disease [4,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation